Electrolyte solution, electrochemical device, and electronic device
By using electrolyte with a specific component ratio in lithium metal batteries, the problems of long circulation and low expansion of lithium metal batteries are solved, and higher circulation performance and lower expansion rates are achieved.
Patent Information
- Application Number
- CN202510120726.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-18
AI Technical Summary
The existing electrolytes are difficult to meet the needs of lithium metal batteries for long cycles and low expansion.
An electrolyte solution is provided, including a first component, a second component and a first lithium salt. By controlling the mass proportion of the components, the ionic conductivity and oxidation stability of the electrolyte solution are improved, and uniform and dense deposition of lithium metal is promoted.
It significantly improves the maximum cycling and expansion performance of lithium metal batteries and extends the service life of the battery.
Smart Images

Figure CN119852530A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to an electrolyte, an electrochemical device using the electrolyte, and an electronic device using the electrochemical device. Background Art
[0002] Lithium metal batteries are considered to be the next generation of battery systems because of their much higher energy density than traditional lithium-ion batteries. However, there is still no electrolyte that can meet the requirements of lithium metal batteries for long cycles at high rates and low expansion. Summary of the invention
[0003] The present application provides an electrolyte, an electrochemical device and an electronic device, which can improve the high-rate cycle performance and expansion performance of a lithium metal battery.
[0004] In a first aspect, the present application provides an electrolyte, comprising a first component, a second component and a first lithium salt, wherein the first component comprises a compound represented by formula (I): (I) R1 is selected from C1 to C4 alkylene and C1 to C4 haloalkylene; R2 and R3 are each independently selected from C1 to C 10 Alkyl and C1 to C 10 The second component comprises at least one of the compounds represented by formula (II) and formula (III): (II) (III), R4 and R5 are each independently selected from C2 to C5 alkyl, and R6 is selected from C5 to C 10 Alkylene; the first lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; wherein, based on the mass of the electrolyte, the mass proportion of the first component is a, the mass proportion of the second component is b, and 0.2≤b / a≤3. When the above-mentioned electrolyte provided in the present application is applied to a lithium metal battery, the first component can efficiently dissociate the lithium salt and improve the ionic conductivity of the electrolyte; the electrolyte containing the second component can dissolve the lithium salt, and its oxidation stability is also high, which improves the stability of the lithium metal battery; the electrolyte containing the first component and the second component and controlling the ratio of b / a to be set within a specific range, under the joint action of the two components, it is helpful to improve the stability of the lithium metal and positive electrode interface while having good lithium metal kinetics in the lithium metal battery, promote the uniform and dense deposition of lithium metal, and improve the high-rate cycle performance and expansion performance of the lithium metal battery.
[0005] Based on the first aspect, in some embodiments, 15%≤a≤60%. The first component has a high solubility in the lithium salt, and the first component is within the above range to reduce the reaction of the first component with lithium metal as much as possible while improving the high ion conductivity of the electrolyte and the stability of the positive / negative electrode interface, thereby further improving the cycle stability and expansion performance of the lithium metal battery at a high rate.
[0006] Based on the first aspect, in some embodiments, 10%≤b≤60%. The second component has relatively lower reactivity with lithium metal and the positive electrode, and can dissolve part of the lithium salt. The mass proportion of the second component is within the above range, which can make the electrolyte have higher ion conductivity while further improving the stability of the electrolyte and the positive / negative electrode, and improve the high-rate cycle life and expansion performance of the lithium metal battery.
[0007] Based on the first aspect, in some embodiments, based on the mass of the electrolyte, the mass proportion of the first lithium salt is c, 20%≤c≤60%. The lithium ions in the first lithium salt can coordinate with the first component and the second component, reducing the reaction between the first component and the lithium metal, and improving the antioxidant capacity of the first component. At the same time, the anions in the first lithium salt are easily dissociated, so that the electrolyte has a higher ionic conductivity; the anions of the first lithium salt can also compete with the solvent in the electrolyte for the coordination of lithium ions, decompose at the positive / negative electrode interface to form a low-impedance SEI film rich in LiF, improve the interface stability of the positive / negative electrode and the lithium ion transmission rate, thereby facilitating the improvement of the cycle stability and expansion performance of the lithium metal battery at a high rate.
[0008] Based on the first aspect, in some embodiments, 0.4≤c / a≤3.0, which can further improve the ionic conductivity and positive / negative electrode stability of the electrolyte, and enhance the high-rate cycle performance and expansion performance of the lithium metal battery.
[0009] Based on the first aspect, in some embodiments, 1≤b / a≤2. The cycle stability and expansion performance of the lithium metal battery at a high rate can be further improved.
[0010] Based on the first aspect, in some embodiments, the electrolyte further includes a second lithium salt, and the second lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, and lithium difluorobis(oxalatophosphate); based on the mass of the electrolyte, the mass proportion of the second lithium salt is d, 0.2%≤d≤5%. This can further improve the interface stability of the positive / negative electrodes of the lithium metal battery, and enhance the high-rate cycle performance and expansion performance of the lithium metal battery.
[0011] Based on the first aspect, in some embodiments, 0.005≤d / (a+b)≤0.1. Controlling the mass ratio of the second lithium salt to the first component and the second component within the above range is conducive to further improving the high-rate cycle performance and expansion inhibition performance of the lithium metal battery.
[0012] Based on the first aspect, in some embodiments, the electrolyte further includes a third component, the third component includes at least one of a fluorinated ether compound, a fluorinated aromatic compound or a fluorinated alkane; based on the mass of the electrolyte, the mass proportion of the third component is e, 10%≤e≤50%. The third component, as a diluent, does not participate in the coordination of lithium ions, and can weaken the coordination of the first component with lithium ions, which is beneficial to further improve the positive / negative electrode stability of the electrolyte, and is also beneficial to improve the viscosity and wettability of the electrolyte, thereby improving the high-rate cycle performance and expansion performance of the lithium metal battery.
[0013] Based on the first aspect, in some embodiments, the third component includes at least one of the compounds represented by formula (IV-1) to formula (IV-14): (IV-1), (IV-2), (IV-3), (IV-4), (IV-5), (IV-6), (IV-7), (IV-8), (IV-9), (IV-10) (IV-11), (IV-12), (IV-13), (IV-14) This is beneficial to further improve the positive / negative electrode stability of the electrolyte, and is also beneficial to improve the viscosity and wettability of the electrolyte, thereby improving the high-rate cycle performance and expansion performance of the lithium metal battery.
[0014] Based on the first aspect, in some embodiments, the first component includes at least one of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dipropyl ether, ethylene glycol dibutyl ether, ethylene glycol methyl ethyl ether, 1,2-propylene glycol dimethyl ether, 1,3-propylene glycol dimethyl ether or dimethoxymethane. The above-mentioned first component can improve the ionic conductivity of the electrolyte, thereby facilitating the high-rate cycle performance of the lithium metal battery.
[0015] Based on the first aspect, in some embodiments, the second component includes at least one of ethyl ether, propyl ether, isopropyl ether, ethyl propyl ether, butyl ether or tetrahydropyran, which can improve the stability of the electrolyte and the positive / negative electrodes, and enhance the high-rate cycle life and expansion performance of the lithium metal battery.
[0016] The third aspect of the present application also provides an electrochemical device, the electrochemical device includes a negative electrode plate and an electrolyte, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer includes at least one of lithium metal or lithium alloy; the lithium alloy includes at least one of lithium tin, lithium zinc, lithium aluminum, lithium magnesium, lithium silver, lithium gold, lithium gallium, lithium indium, lithium platinum, lithium boron, lithium carbon or lithium silicon alloy. It is beneficial to further improve the high-rate cycle life and expansion performance of lithium metal batteries.
[0017] Based on the first aspect, in some embodiments, the thickness of the negative electrode material layer is X μm, and c and X satisfy: 0.004≤c / X≤0.04, which is beneficial to further improve the high-rate cycle performance and expansion performance of the lithium metal battery.
[0018] The third aspect of the present application also provides an electronic device, including an electrochemical device. The electrochemical device contains the electrolyte, which can improve the high-rate cycle performance and expansion performance of the electrochemical device, thereby increasing the service life of the electronic device. DETAILED DESCRIPTION
[0019] The technical scheme in the embodiment of the present application is described clearly and in detail below. Obviously, the described embodiment is a part of the embodiment of the present application, rather than all the embodiments. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.
[0020] An embodiment of the present application provides an electrochemical device, which includes a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.
[0021] The outer shell may be a packaging bag encapsulated by a packaging film (such as an aluminum-plastic film), for example, the electrochemical device is a soft-pack battery.
[0022] The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet. The electrode assembly may be a laminated structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet and then winding them.
[0023] Positive electrode There is no particular limitation on the positive electrode sheet in the present application, as long as the purpose of the present application can be achieved. The positive electrode sheet generally comprises a positive current collector and a positive active material. The above-mentioned positive current collector is not particularly limited, and may be any positive current collector known in the art, such as copper foil, aluminum foil, aluminum alloy foil, and composite current collector. The above-mentioned positive active material is not particularly limited, and may be any positive active material of the prior art, for example, it may include at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, or lithium iron manganese phosphate.
[0024] In the present application, the thickness of the positive electrode current collector and the positive electrode active material is not particularly limited as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 8 μm to 12 μm, and the thickness of the positive electrode active material is 30 μm to 120 μm.
[0025] In the present application, the positive electrode material layer may also include a conductive agent, and the present application has no particular restrictions on the conductive agent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of conductive carbon black (SuperP), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metal materials or conductive polymers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.
[0026] In the present application, the positive electrode active material layer may also include a binder. There is no particular limitation on the binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, nylon, etc.
[0027] Optionally, the positive electrode may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a commonly used conductive layer in the art, for example, including but not limited to the above conductive agent and the above binder.
[0028] Negative electrode The negative electrode plate includes a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector, the negative electrode material layer includes at least one of lithium metal or lithium alloy; the lithium alloy includes at least one of lithium tin, lithium zinc, lithium aluminum, lithium magnesium, lithium silver, lithium gold, lithium gallium, lithium indium, lithium platinum, lithium boron, lithium carbon or lithium silicon alloy.
[0029] The negative electrode current collector is used to carry the negative electrode material layer and conduct current, and the shape can be a foil or a mesh. The material of the negative electrode current collector includes at least one of copper foil, titanium foil, stainless steel, carbon paper or graphene paper.
[0030] In the present application, the negative electrode material layer may further include a conductive agent. The present application has no particular limitation on the conductive agent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of the above conductive agents.
[0031] In the present application, the negative electrode material layer may further include a binder. The present application has no particular limitation on the binder, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of the above-mentioned binders.
[0032] Optionally, the negative electrode may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a commonly used conductive layer in the art, and may include but is not limited to the above conductive agent and the above binder.
[0033] Isolation film The material and shape of the separator used in the electrochemical device of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0034] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.
[0035] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.
[0036] The binder is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).
[0037] Electrolyte The present application provides an electrolyte, the electrolyte comprising a first component, a second component and a first lithium salt, the first component comprising a compound represented by formula (I) (I) R1 is selected from C1 to C4 alkylene and C1 to C4 haloalkylene; R2 and R3 are each independently selected from C1 to C 10 Alkyl and C1 to C 10 Haloalkyl; The second component includes at least one of the compounds represented by formula (II) and formula (III): (II) (III) R4 and R5 are each independently selected from C2 to C5 alkyl, and R6 is selected from C5 to C 10 an alkylene group; the first lithium salt comprises at least one of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI); Wherein, based on the mass of the electrolyte, the mass proportion of the first component is a, the mass proportion of the second component is b, and 0.2≤b / a≤3.
[0038] When the above-mentioned electrolyte provided in the present application is applied to a lithium metal battery, the first component can efficiently dissociate the lithium salt, thereby improving the ionic conductivity of the electrolyte; the electrolyte containing the second component can dissolve the lithium salt, and its oxidation stability is also relatively high, thereby improving the stability of the lithium metal battery; the electrolyte provided in the present application contains the first component and the second component and controls the ratio of b / a to be within the range of 0.2≤b / a≤3. Under the joint action of the two components, it is helpful to improve the interface stability between the lithium metal and the positive electrode while having good lithium metal kinetics in the lithium metal battery, promote the uniform and dense deposition of the lithium metal, and enhance the high-rate cycle performance and expansion performance of the lithium metal battery.
[0039] If b / a is small, such as b / a<0.2, the relative content of the second component is low, which has little effect on improving the stability of the lithium metal and positive electrode interface, and is not conducive to improving the cycle stability and expansion inhibition performance of lithium metal batteries at high rates. If b / a is large, such as b / a>3, the relative content of the first component is low, which will deteriorate the dynamics of lithium metal batteries, is not conducive to the uniform and dense deposition of lithium metal, and will reduce the high-rate cycle stability of lithium metal batteries.
[0040] In some embodiments, the ratio of b / a can be 0.2, 0.3, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.6, 1.6, 2, 2.2, 2.5, 2.7, 2.9, 3 or any value within the range formed by any two of the above values.
[0041] In some embodiments, 1≤b / a≤2. When b / a is within this suitable range, the cycle stability and expansion performance of the lithium metal battery at a high rate can be further improved.
[0042] In some embodiments, 15%≤a≤60%. The first component has a high solubility in lithium salts. The first component is within the above range to reduce the reaction of the first component with lithium metal as much as possible while improving the high ionic conductivity of the electrolyte and the stability of the positive / negative electrode interface, thereby facilitating the improvement of the cycle stability and expansion performance of lithium metal batteries at high rates. If a<15%, the ionic conductivity of the electrolyte is too low, and the effect of further improving the high-rate cycle stability of lithium metal batteries is not obvious. If a>60%, the stability of the electrolyte and the positive / negative electrode interface will be reduced, and the effect of improving the high-rate cycle stability of lithium metal batteries will also be not obvious. In some embodiments, the a value can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or any value within the range of any two of the above values.
[0043] In some embodiments, 10%≤b≤60%. The reaction activity of the second component with lithium metal and the positive electrode is relatively lower, and it can dissolve part of the lithium salt. The mass proportion of the second component is within the above range, which can make the electrolyte have a higher ionic conductivity while further improving the stability of the electrolyte and the positive / negative electrode, and improving the high-rate cycle life and expansion performance of the lithium metal battery. If b<10%, the electrolyte containing the second component has no obvious improvement on the positive and negative electrode stability of lithium metal, and the effect of further improving the high-rate cycle stability of the lithium metal battery is not obvious. If b>60%, the ionic conductivity of the electrolyte will be reduced, the kinetics of lithium metal will be reduced, and the effect of further improving the high-rate cycle stability and expansion performance of the lithium metal battery will not be obvious. In some embodiments, the b value can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any value within the range composed of any two of the above values.
[0044] In some embodiments, based on the mass of the electrolyte, the mass proportion of the first lithium salt is c, 20%≤c≤60%. The lithium ions in the first lithium salt can coordinate with the first component and the second component, reducing the reaction between the first component and the lithium metal, and improving the antioxidant capacity of the first component. At the same time, the anions in the first lithium salt are easily dissociated, so that the electrolyte has a higher ionic conductivity; the anions in the first lithium salt can also compete with the solvent in the electrolyte to coordinate lithium ions, decompose at the positive / negative electrode interface to form a low-impedance SEI film rich in LiF, improve the interface stability and lithium ion transfer rate of the positive / negative electrode, thereby improving the cycle stability and expansion performance of the lithium metal battery at a high rate. Controlling the mass proportion of the first lithium salt within the above range is conducive to making the electrolyte have a suitable solvation structure, improving the positive / negative electrode interface film structure, reducing the side reactions of the positive / negative electrode, and facilitating the lithium ion to have a higher lithium ion transfer rate at both the electrolyte and the positive / negative electrode interface, thereby improving the high-rate cycle stability and expansion performance of the lithium metal battery. If c < 20%, the lithium ion concentration in the electrolyte is low, and the effect on improving the high-rate cycle performance of the lithium metal battery is not obvious; if c > 60%, the lithium ion concentration in the electrolyte is too high, the viscosity of the electrolyte is large, the wettability is reduced, and thus the conductivity of the lithium ions is reduced, and the effect on improving the high-rate cycle performance and expansion performance of the lithium metal battery is not obvious. In some embodiments, the c value can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or any value within the range of any two of the above values.
[0045] In some embodiments, 0.4≤c / a≤3.0. The mass ratio of the first lithium salt and the first component is within the above range, which can further improve the ionic conductivity and positive / negative electrode stability of the electrolyte, and enhance the high-rate cycle performance and expansion performance of the lithium metal battery. If c / a<0.4, the positive / negative electrode stability of the electrolyte will be reduced, and the effect on improving the high-rate cycle stability and expansion performance of the lithium metal battery will not be obvious; if c / a>3.0, the viscosity of the electrolyte is high, which reduces the ionic conductivity, and the effect on improving the high-rate cycle performance and expansion performance of the lithium metal battery is not obvious. In some embodiments, the c / a value can be 0.4, 0.7, 0.9, 1, 1.2, 1.5, 1.7, 1.9, 2, 2.5, 3.0 or any value within the range formed by any two of the above values.
[0046] In some embodiments, the electrolyte further includes a second lithium salt, and the second lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorooxalate borate (LiDFOB) and lithium difluorobis(oxalate) phosphate (LiDFBP). Based on the mass of the electrolyte, the mass proportion of the second lithium salt is d, 0.2%≤d≤5%. The mass proportion of the second lithium salt is within the above range, and it participates in the formation of the SEI film in the lithium metal battery, which can further improve the ionic conductivity and the interface stability of the positive / negative electrode of the lithium metal battery, and improve the high-rate cycle performance and expansion performance of the lithium metal battery. If d<0.2%, the content of the second lithium salt is small, the participation of the second lithium salt in the film formation is low, and the effect of further improving the stability of the interface film is not obvious; if d>5%, the electrolyte containing the second lithium salt has a reduced improvement effect on the positive / negative electrode interface film, and at the same time reduces the ionic conductivity of the electrolyte, and the effect of improving the high-rate cycle performance and expansion performance of the lithium metal battery is not obvious. In some embodiments, d can be 0.2%, 0.3%, 0.5%, 1%, 1.2%, 1.6%, 2.2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 4.8%, 5%, or any value within the range formed by any two of the above values.
[0047] In some embodiments, 0.005≤d / (a+b)≤0.1. Controlling the mass ratio of the second lithium salt to the first component and the second component within the above range is beneficial to further improve the high-rate cycle performance and inhibit expansion performance of the lithium metal battery. If d / (a+b)<0.005, the content of the second lithium salt is relatively small, which is not conducive to the participation of the second lithium salt in film formation, and the effect on improving the high-rate cycle performance and expansion performance of the lithium metal battery is not obvious; if d / (a+b)>0.1, it will reduce the improvement effect of the electrolyte on the positive / negative electrode interface film, and will significantly reduce the ionic conductivity of the electrolyte, and the effect on the high-rate cycle performance and expansion performance of the lithium metal battery is not obvious. In some embodiments, the ratio of d / (a+b) can be 0.005, 0.007, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value within the range formed by any two of the above values.
[0048] In some embodiments, the electrolyte further includes a third component, the third component includes at least one of a fluorinated ether compound, a fluorinated aromatic compound or a fluorinated alkane; based on the mass of the electrolyte, the mass proportion of the third component is e, 10%≤e≤50%. In the present application, the third component, as a diluent, does not participate in the coordination of lithium ions, and can weaken the coordination of the first component with lithium ions, which is beneficial to further improve the positive / negative electrode stability of the electrolyte, and is also beneficial to improve the viscosity and wettability of the electrolyte, thereby improving the high-rate cycle performance and expansion performance of the lithium metal battery. At the same time, controlling the mass proportion of the third component within the above range can further improve the viscosity, wettability and positive / negative electrode stability of the electrolyte, and improve the high-rate cycle life and expansion performance of the lithium metal battery. If e<10%, the content of the third component has no obvious effect on improving the viscosity, wettability and positive / negative electrode stability of the electrolyte, and has little effect on improving the high-rate cycle life of the lithium metal battery. If e>50%, the mass proportion of the diluent is too high, which will reduce the migration rate of lithium ions and have little effect on improving the high-rate cycle performance and expansion performance of lithium metal batteries. In some embodiments, e can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any value within the range of any two of the above values.
[0049] In some embodiments, the third component includes at least one of the compounds represented by formula (IV-1) to formula (IV-14): (IV-1), (IV-2), (IV-3), (IV-4), (IV-5), (IV-6), (IV-7), (IV-8), (IV-9), (IV-10) (IV-11), (IV-12), (IV-13), (IV-14). The above-mentioned substance is the third component. As a diluent, the third component does not participate in the coordination of lithium ions, but can also weaken the coordination between the first component and lithium ions, which is beneficial to further improve the positive / negative electrode stability of the electrolyte, and is also beneficial to improve the viscosity and wettability of the electrolyte, and improve the high-rate cycle performance and expansion performance of the lithium metal battery.
[0050] In some embodiments, the first component includes at least one of ethylene glycol dimethyl ether (DME), ethylene glycol diethyl ether (DEE), ethylene glycol dipropyl ether (DPE), ethylene glycol dibutyl ether (DBE), ethylene glycol methyl ethyl ether (MEE), 1,2-propylene glycol dimethyl ether (1,2-DMP), 1,3-propylene glycol dimethyl ether (1,3-DMP) or dimethoxymethane (DMM). The above first components can dissociate lithium salts and improve the ionic conductivity of the electrolyte, thereby improving the high-rate cycle performance of lithium metal batteries.
[0051] In some embodiments, the second component includes at least one of ethyl ether (EE), propyl ether (PE), isopropyl ether (IPE), ethyl propyl ether (EPE), butyl ether (BE) or tetrahydropyran (THP). The second component has low reactivity to lithium metal and positive electrode materials and high stability, and can improve the stability of the electrolyte and positive / negative electrodes, and enhance the high-rate cycle life and expansion performance of lithium metal batteries.
[0052] In some embodiments, the thickness of the negative electrode material layer is Xμm, satisfying 0.004≤c / X≤0.04. Controlling the mass ratio of the first lithium salt and the thickness of the negative electrode material layer within the above range can further improve the high-rate cycle performance and expansion performance of the lithium metal battery. If c / X<0.004, the first lithium salt will be consumed rapidly during the cycle process, which will have a greater impact on the later film formation of the high-rate cycle process of the lithium metal battery, and will have little effect on improving the high-rate cycle and expansion performance of the lithium metal battery; if c / X>0.04, lithium metal will be consumed rapidly during the cycle process, and the effect on improving the high-rate cycle performance of the lithium metal battery is not obvious. In some embodiments, the ratio of c / X can be 0.004, 0.008, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04 or any value within the range composed of any two of the above values.
[0053] According to some embodiments of the present application, the electrochemical device of the present application includes, but is not limited to: a lithium metal battery or a sodium ion battery. In some embodiments, the electrochemical device includes a lithium metal battery.
[0054] The present application also applies electrochemical devices to electronic devices to power loads in the electronic devices. The above-mentioned electronic device includes an electrochemical device, and the electrochemical device contains the electrolyte, which can improve the high-rate cycle performance and expansion performance of the electrochemical device, thereby improving the service life of the electronic device. The electronic equipment or device of the present application is not particularly limited. In some embodiments, the electronic equipment of the present application includes, but is not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0055] The present application is described below by specific examples and comparative examples. Those skilled in the art should understand that the preparation methods described in the present application are only examples, and any other suitable preparation methods are within the scope of the present application.
[0056] Example 1 <Preparation of soft pack batteries> (1) Preparation of positive electrode The positive electrode active material NCM811 (LiNi 0.8 Mn 0.1 Co 0.1 O2), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:2:2, N-methylpyrrolidone (NMP) is added as a solvent, and a slurry with a solid content of 75% is prepared, and the slurry is stirred under the action of a vacuum mixer until the system becomes a uniform positive electrode slurry. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm and dried at 90°C. After the above steps are completed, the single-sided coating of the positive electrode plate is completed. After that, the above steps are repeated on the other surface of the positive electrode plate to obtain a positive electrode plate coated with positive electrode active material on both sides. After the coating is completed, the positive electrode plate is cold pressed and cut into the required specifications for standby use. After testing, the single-sided thickness of the active material layer of the positive electrode plate is 60μm, and the single-sided capacity is 4mAh / cm 2 .
[0057] (2) Preparation of negative electrode A metal lithium foil is placed on one surface of a negative electrode current collector copper foil with a thickness of 8 μm, and a roller is pressed with an appropriate force to make the metal lithium and the current collector adhere to each other, thereby obtaining a negative electrode sheet with a single-sided lithium foil loaded with a thickness of 20 μm.
[0058] (3) Preparation of electrolyte In an argon atmosphere glove box with a water content of <10 ppm, the components were mixed in the proportions shown in Table 1 to form an electrolyte.
[0059] (4) Isolation film A polyethylene (PE) porous polymer with a thickness of 12 μm was used as the isolation membrane.
[0060] (5) Assembly of lithium metal batteries The positive electrode sheet and the negative electrode sheet are connected to the tabs respectively, and then stacked in the order of single-sided negative electrode sheet, separator, double-sided positive electrode sheet, separator, and single-sided negative electrode sheet, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of isolation. Then, after winding and welding the tabs, they are placed in the outer packaging foil aluminum plastic film, and the electrolyte is injected. After vacuum packaging, standing, formation, capacity testing and degassing, a lithium metal battery is obtained.
[0061] Examples 2 to 30 The preparation methods of Examples 2 to 30 are substantially the same as those of Example 1, except that the composition and content of the remaining components in the electrolyte and the preparation parameters are recorded in Tables 1 to 5.
[0062] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the electrolyte does not contain the second component. The preparation parameters are recorded in Table 1.
[0063] Comparative Examples 2 to 3 The preparation methods of Comparative Examples 2 to 3 are substantially the same as those of Example 1, except that the composition and content of the remaining components in the electrolyte and the preparation parameters are recorded in Table 1.
[0064] The thickness of the negative electrode material layer was tested for the lithium metal batteries assembled in Examples 1 to 30 and Comparative Examples 1 to 3.
[0065] Method for measuring the thickness of the negative electrode material layer: The lithium metal battery was disassembled to obtain the negative electrode sheet. The cross section of the negative electrode sheet was exposed by argon ion milling (CP), and then the thickness of the single side of the negative electrode active material was observed and measured by a scanning electron microscope (SEM).
[0066] The lithium metal batteries assembled with the electrolytes prepared in the examples and comparative examples were subjected to high rate cycling and expansion rate tests, and the test results are recorded in Tables 1 to 5. Performance test of lithium metal battery: (1) High-rate cycling performance At 25±5℃ and normal pressure, the prepared lithium metal battery was charged to 4.3V at 1C rate constant current, then charged to 0.05C at constant voltage, left to stand for 5min, discharged to 2.8V at 1C rate constant current, left to stand for 5min, this is a charge and discharge cycle process, and the first cycle discharge capacity C0 was recorded. Perform 200 cycles of charge and discharge test in the above manner, and record the 200th cycle discharge capacity C1.
[0067] High-rate cycle capacity retention rate = C1 / C0×100%.
[0068] (2) Expansion rate test: Before the high-rate cycle test (1) of the lithium metal battery, the prepared lithium metal battery was charged to 4.3V at a constant current of 0.2C at 25±5°C and normal pressure, and then charged to a current of 0.05C at a constant voltage, and allowed to stand for 5 minutes. The initial thickness T0 of the lithium metal battery was recorded, and then discharged to 2.8V at 1C, and then a high-rate cycle test was performed (1).
[0069] After the lithium metal battery has undergone 200 cycles of high-rate cycling test (1), the prepared lithium metal battery is charged at a constant current of 0.2C to 4.3V at 25±5℃ and normal pressure, and then charged at a constant voltage to a current of 0.05C. After standing for 5 minutes, the post-cycle thickness T1 of the lithium metal battery is recorded, and then discharged at 1C to 2.8V.
[0070] Expansion rate = (T1-T0) / T0×100%.
[0071] Table 1 shows the test results of the examples and comparative examples. “ / ” in the table means it has not been added or does not exist.
[0072] In Table 1, compared with Comparative Examples 1 to 3, in Examples 1 to 17, when the first component, the second component and the first lithium salt satisfy the specific components and the mass ratio of the first component and the second component satisfies the relationship of 0.2≤b / a≤3, the high-rate cycle performance and expansion performance of the lithium metal battery are significantly improved. In this electrolyte, the first component and the second component work together to help improve the stability of the lithium metal and positive electrode interface while the lithium metal battery has good lithium metal kinetics, and promote the uniform and dense deposition of lithium metal, thereby improving the high-rate cycle performance and expansion performance of the lithium metal battery.
[0073] In Examples 1 to 17, when the mass proportions of the first group, the second component, and the first lithium salt are within a specific range, and the c / a ratio is within a specific range, the corresponding lithium metal batteries have good high-rate cycle performance and expansion performance.
[0074] Table 2 Combined with Table 2, in Examples 18 to 22, by adding the second lithium salt to the electrolyte, it was found that the high-rate cycle performance and expansion performance of the lithium metal battery were significantly improved. In the lithium metal battery, the second lithium salt will participate in the formation of the SEI film in the lithium metal battery, which can further improve the ion conductivity of the lithium metal battery and the interface stability of the positive / negative electrodes, thereby improving the high-rate cycle performance and expansion performance of the lithium metal battery.
[0075] In Examples 18 to 22, when 0.2%≤d≤5% and 0.005≤d / (a+b)≤0.1, the corresponding lithium metal batteries have good high-rate cycle performance and expansion performance.
[0076] Table 3 In Table 3, in Examples 23 to 25, the electrolyte contains a third component, and the mass proportion of the third component satisfies 10%≤e≤50%, which significantly improves the high-rate cycle performance and expansion performance of the corresponding lithium metal battery.
[0077] Table 4 In the above Table 4, in Example 5 and Examples 26 to 28, the thickness of the negative electrode material layer is changed, and c / X is made to meet a specific range, and the corresponding lithium metal batteries have good high-rate cycle performance and expansion performance.
[0078] Table 5 In Table 5, in Examples 29 to 30, the electrolyte comprises a first component, a second component, a first lithium salt, a second lithium salt and a third component, and their respective mass proportions meet specific conditions, which significantly improves the high-rate cycle performance and expansion performance of the lithium metal battery.
[0079] The above disclosure is only a preferred implementation mode of the present application, and certainly cannot be used to limit the present application. Therefore, equivalent changes made according to the present application are still within the scope covered by the present application.
Claims
1. An electrolyte, characterized in that: The invention comprises a first component, a second component and a first lithium salt, wherein the first component comprises a compound represented by formula (I): (I) R1 is selected from C1 to C4 alkylene and C1 to C4 haloalkylene; R2 and R3 are each independently selected from C1 to C 10 Alkyl and C1 to C 10 Haloalkyl; The second component includes at least one of the compounds represented by formula (II) and formula (III): (II) (III) R4 and R5 are each independently selected from C2 to C5 alkyl, and R6 is selected from C5 to C 10 Alkylene; The first lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; Wherein, based on the mass of the electrolyte, the mass proportion of the first component is a, the mass proportion of the second component is b, and 0.2≤b / a≤3.
2. The electrolyte according to claim 1, characterized in that Based on the mass of the electrolyte, the mass proportion of the first lithium salt is c, and the electrolyte satisfies at least one of the following conditions: (1)15%≤a≤60%; (2)10%≤b≤60%; (3)20%≤c≤60%; (4) 0.4≤c / a≤3.
0.
3. The electrolyte according to claim 1, characterized in that 1≤b / a≤2.
4. The electrolyte according to claim 1, characterized in that The electrolyte further includes a second lithium salt, wherein the second lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium difluorobisoxalatophosphate; Based on the mass of the electrolyte, the mass proportion of the second lithium salt is d, 0.2%≤d≤5%.
5. The electrolyte according to claim 4, characterized in that 0.005≤d / (a+b)≤0.
1.
6. The electrolyte according to claim 1, characterized in that The electrolyte further includes a third component, the third component including at least one of a fluorinated ether compound, a fluorinated aromatic compound or a fluorinated alkane; Based on the mass of the electrolyte, the mass proportion of the third component is e, 10%≤e≤50%.
7. The electrolyte according to claim 6, characterized in that The electrolyte satisfies at least one of the following conditions: (1) The third component includes at least one of the compounds represented by formula (IV-1) to formula (IV-14): (IV-1)、 (IV-2)、 (IV-3)、 (IV-4)、 (IV-5)、 (IV-6)、 (IV-7)、 (IV-8)、 (IV-9)、 (IV-10) 、 (IV-11)、 (IV-12)、 (IV-13)、 (IV-14); (2) the first component includes at least one of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dipropyl ether, ethylene glycol dibutyl ether, ethylene glycol methyl ethyl ether, 1,2-propylene glycol dimethyl ether, 1,3-propylene glycol dimethyl ether or dimethoxymethane; (3) The second component comprises at least one of ethyl ether, propyl ether, isopropyl ether, ethyl propyl ether, butyl ether or tetrahydropyran.
8. An electrochemical device comprising a negative electrode plate, characterized in that: The electrochemical device also includes an electrolyte as described in any one of claims 1 to 7, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector, the negative electrode material layer includes at least one of lithium metal or lithium alloy; the lithium alloy includes at least one of lithium tin, lithium zinc, lithium aluminum, lithium magnesium, lithium silver, lithium gold, lithium gallium, lithium indium, lithium platinum, lithium boron, lithium carbon or lithium silicon alloy.
9. The electrochemical device according to claim 8, characterized in that Based on the mass of the electrolyte, the mass proportion of the first lithium salt is c, the thickness of the negative electrode material layer is X μm, and c and X satisfy: 0.004≤c / X≤0.
04.
10. An electronic device, characterized in that: Comprising the electrochemical device as claimed in claim 8 or 9.